Research on the Solution of Business Platform Security - Yanchun Wang; Hong Li (Dianxin kexue)
As an important support system,it is necessary for the telecommunication service platform to ensure the security of service system and the information data,and to try to avoid the negative effects brought by security events and economic loss.Based on the research and analysis,several typical problems of safety telecommunications business platform,and the entry point for the process,were studied.At last,with two aspects of management and technology,the solution to security problems of service platform was discussed.